Implementation of Mobile Customer Relationship Management (mCRM) in Belarusian Market - Astraukh, Kate (2009)
Abstract: Customer Relationship Management (CRM) and Mobile Marketing (MM) are two areas of business that have been given considerable attention by academics and marketing practitioners in recent years (Agnihothri et al., 2002). The research done by Varian et al., (2006) shows that CRM applications are among the most widely adopted business solutions in the private sector today. The area of Mobile CRM has grown substantially in recent years from a $120 million industry in 2001 to a $1.7 billion industry in 2005 (Research and Markets, 2006). The purpose of this research is to investigate the application of Mobile Customer Relationship Management on the Belarusian Market. The investigation will start with a literature review, which will be divided into two chapters. The first chapter will review literature relating to the research agenda, starting with a brief look at the emergence of the traditional marketing concept and its paradigm shift towards Relationship Marketing. After evaluating relationship marketing, a CRM overview will be conducted, looking at the advantages and problems of CRM implementation within an organisation. This will lead to the primary focus of this research, namely Mobile Customer Relationship Management. The second part the literature review will review existing literature on Mobile CRM and highlight the importance of recent mobile technological development. This will lead to a conceptualization of Mobile CRM. Following this, focus will shift to the unique characteristics of Mobile CRM, followed by a discussion of the advantages and limitations that organizations may faced in implementing Mobile CRM. Finally, the practical implementations of Mobile CRM will be examined in the form of an analysis of a representative set of case studies. For the nature of this research, qualitative research methodology has been chosen. The researcher has conducted 5 in-depth interviews to collect data concerning the implementation of the Mobile CRM application on the Belarusian market. Analysis will be conducted from three different angles: 1) Mobile Networks Providers, 2) Mobile Marketing agencies, and 3) a company who was engaging the mobile medium in segmenting, targeting and communicating with its customers. The data from the interviews has been analyzed and discussed through thematic division. The conclusion will focus on infrastructural readiness in relation to individual business uptake of Mobile CRM.